2002
DOI: 10.1074/jbc.m205870200
|View full text |Cite
|
Sign up to set email alerts
|

CaT1 Contributes to the Stores-operated Calcium Current in Jurkat T-lymphocytes

Abstract: T-lymphocyte activation requires sustained

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 45 publications
3
61
0
Order By: Relevance
“…It is possible that no single Trp family protein alone forms the I CRAC channel, rather that there is a heteromultimeric channel formed from an assemblage of various Trp proteins. In support of this Cui et al (10) found that Jurkat T lymphocytes express both TrpV1 and TrpV5 (ECaC1) in addition to TrpV6 and suggested that TrpV5 contributed to the I CRAC current. Furthermore, Philipp et al (12) isolated a series of random mutants of Jurkat T cells with defects in TCR-dependent Ca 2ϩ entry.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…It is possible that no single Trp family protein alone forms the I CRAC channel, rather that there is a heteromultimeric channel formed from an assemblage of various Trp proteins. In support of this Cui et al (10) found that Jurkat T lymphocytes express both TrpV1 and TrpV5 (ECaC1) in addition to TrpV6 and suggested that TrpV5 contributed to the I CRAC current. Furthermore, Philipp et al (12) isolated a series of random mutants of Jurkat T cells with defects in TCR-dependent Ca 2ϩ entry.…”
supporting
confidence: 50%
“…Mammalian homologues of the Drosophila Trp proteins have been reported to be expressed in Jurkat T lymphocytes (7,8). The TrpV family member TrpV6 (CaT1) is the strongest contender for the I CRAC channel (9,10) although this has been disputed (11). It is possible that no single Trp family protein alone forms the I CRAC channel, rather that there is a heteromultimeric channel formed from an assemblage of various Trp proteins.…”
mentioning
confidence: 99%
“…It was shown that the enzyme hydrolyzes and activates the TRPV5 channel conducting K ϩ (52) and hydrolyzes steroid ␤-glucuronides (10). Channels belonging to the TRPV family are present in the T cell membranes and might be involved in the immune cells' activation (53). Thus, possible lack of their activation related to decreased or even nullified Klotho activity could be one of the causes of impaired activation of the T cells both in healthy aged people as well as in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it still remains possible that CRAC channels are formed with a heterologous combination of different trp proteins (see (Venkatachalam et al, 2002) for a recent review). Involvement of CaT1 (TRPV6) in such a combination has been strongly suggested in Jurkat T cells (Cui et al, 2002;Yue et al, 2001).…”
Section: Ca 2+ Influxmentioning
confidence: 99%